Influence of target curvature on ion acceleration in radiation pressure acceleration regime. (17th March 2015) - Dahiya, Deepak; Kumar, Ashok; Tripathi, V. K.
Abstract Ion acceleration from submicron thick foil target irradiated by a circularly polarized laser is studied using multidimensional particle-in-cell simulations. Convex, flat, and concave target shapes are considered. Radius of curvature of curved target is of the order of laser width in transverse direction. Accelerated ion beam of highest peak energy and least energy spread is obtained from concave target, whereas total accelerated charge is highest in convex target. It is attributed to the change in the growth of transverse instabilities and geometrical effects due to target curvature in initial stages of acceleration process. The variation in the radius of curvature of the foil depends on the ratio of initial spot size to the radius of curvature. Faster reduction in curvature is achieved for tightly focused Gaussian pulses as conjectured by the model.